1984
DOI: 10.1007/bf00287640
|View full text |Cite
|
Sign up to set email alerts
|

Red cell glutathione peroxidase (GPX1) variation in Afro-Jamaican, Asiatic Indian, and Dutch populations

Abstract: A Cellogel procedure for screening the electrophoretic variants of the human red cell glutathione peroxidase ( GPX1 ) was described. Three hundred and ninety eight Dutch persons living in various parts of The Netherlands, 385 individuals born in various states of India, and 72 Jamaicans of African origin living in Birmingham, UK, were screened for GPX1 variants. The Dutch were monomorphic, while one Afro-Jamaican female and two males and one female of the 116 Punjabis were found to be variants indistinguishabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Erythrocyte and serum polymorphisms (the abbreviation is followed by the reference to the electrophoretic technique used) analyzed were: 6-phosphogluconate dehydrogenase (6-PGD; Sonneborn et al, 1972); acid phosphatase locus 1 (ACP1; Destro-Bisol and Ranalletta, 1988); ␣ 1 -antitrypsin (A1-AT; Pascali and De Mercurio, 1981); carbonic anhydrase locus II (CAII; Noppinger and Morrison, 1981); esterase D (ESD; Destro- Bisol and Spinella, 1989); glyoxalase locus I (GLOI; Meera Khan and Doppert, 1976); group specific component (GC; Pascali et al, 1984); glutathione peroxidase (GPX1; Meera Khan et al, 1984); phosphoglucomutase locus 1 (PGM1; Destro-Bisol and Spinella, 1989); transferrin (TF; Pascali et al, 1988). 6-PGD, CAII, GLOI and GPX1 were typed by conventional electrophoresis on gelled cellulose acetate strips (Cellogel).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Erythrocyte and serum polymorphisms (the abbreviation is followed by the reference to the electrophoretic technique used) analyzed were: 6-phosphogluconate dehydrogenase (6-PGD; Sonneborn et al, 1972); acid phosphatase locus 1 (ACP1; Destro-Bisol and Ranalletta, 1988); ␣ 1 -antitrypsin (A1-AT; Pascali and De Mercurio, 1981); carbonic anhydrase locus II (CAII; Noppinger and Morrison, 1981); esterase D (ESD; Destro- Bisol and Spinella, 1989); glyoxalase locus I (GLOI; Meera Khan and Doppert, 1976); group specific component (GC; Pascali et al, 1984); glutathione peroxidase (GPX1; Meera Khan et al, 1984); phosphoglucomutase locus 1 (PGM1; Destro-Bisol and Spinella, 1989); transferrin (TF; Pascali et al, 1988). 6-PGD, CAII, GLOI and GPX1 were typed by conventional electrophoresis on gelled cellulose acetate strips (Cellogel).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Preparation of samples and electrophoretic procedures were performed in accordance with Meera Khan et al (1984a), except that 0.05 M dithiothreitol (DTT) was used as lysis solution instead of 0.1 M 2-mercaptoethanol (2-ME). Samples exhibiting unusual patterns were treated by 0.05 or 0.1 M DTT, 1 M or 2 M 2-ME, or 0.05 M GSH.…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al (1984a) lThe GPXb2 allele was nut found in 110 Norwegians,398 Dutch, and 76 Sardinians(Meera Khan et al, 1984a), 300 non-Jewish whites of the U S A . (estimated by Meera Khan et al, 1984afrom Beutler et al, 1974 and 47 Marathi and 198 Telugu of India (Meera Khan et al, 1984a).…”
Section: Gpxl*2 Allele As Anthropological Markermentioning
confidence: 99%
See 2 more Smart Citations